The pragmatic ideal : Mary Field Parton and the pursuit of a progressive society - McGarvie, Mark D. (Mark Douglas), 1956- (Northern Illinois University Press, an imprint of Cornell University Press, 2022)
"This microhistory uses the life of writer and social activist Mary Field Parton to access the intellectual and cultural movements of the late 1800s and early 1900s and to explore the tensions and inconsistencies within progressivism"--